Prospective surveillance of hospital associated infections epidemiology in a haematology-oncology department - Bouafia, Nabiha; Ammar, Asma; Ezzi, Olfa; Ben Chiekh, Asma; Mahjoub, Mohamed; Bannour, Wadiaa; Helali, Radhia; Achour, Bechir; Ben Salah, Arwa; Dalel, Ben Slimene; et al. (International Journal of Infection Control, 2019)
In haematology-oncology, intensified procedures have been associated with higher risk of healthcare associated infections (HAIs).This study aimed to estimate the incidence and to identify risk factors of HAIs in a haematology-oncology unit in a Tunisian university hospital. We conducted a prospective study, during 06 months from Mars through September 2016 in the department of hematology- oncology in a tertiary teaching hospital in Tunisia. Patients, admitted for ≥48 h, were followed until hospital discharge. The (CDC) criteria for site-specific infections were used to define HAIs. Bivariate and multivariate analyses were performed to identify risk factors of HAIs. P<0.05 was considered as significant. A total of 150 patients were included in this study with mean age; 23.12 ±18.36 years. The overall HAI attack rate of HAIs was 32.6/100 patients with an incidence 15.7 per 1000 patient-days at risk. Nosocomial Fever of Unknown Origin was the most frequent infection (42.9% of total HAI’s). Independent risk factors for developing HAIs were male gender (OR[CI]95%= 4.60[1.43-14.61]; p=0.01), neutropenia (OR[CI]95%=10.20[2.26-45.72],p=0.002), aplasia inducing chemotherapy (OR[CI]95%=6.0 [1.07-33.19], p=0.004) and bone marrow aspiration and biopsy (OR[CI]95%=3.0 [1.10-8.03], p=0.03). In conclusion, our study highlights the burden of HAIs in this unit and the role of surveillance for specific HAIs and analyzing its risk factors. A comprehensive education program focused on evidence-based approaches for all healthcare workers should be implemented in this unit.